2017
DOI: 10.1093/sleep/zsx075
|View full text |Cite
|
Sign up to set email alerts
|

Internet and In-Person Cognitive Behavioral Therapy for Insomnia in Military Personnel: A Randomized Clinical Trial

Abstract: Despite the unique, sleep-disrupting occupational demands of military personnel, in-person and Internet CBTi are efficacious treatments for this population. The effect sizes for in-person were consistently better than Internet and both were similar to those found in civilians. Dissemination of CBTi should be considered for maximum individual and population benefits, possibly in a stepped-care model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 77 publications
4
101
1
1
Order By: Relevance
“…Direkte Vergleichsstudien von internetbasierter KVT-I zu F2F-psychotherapeutischer Behandlung zeigten bislang keine ganz einheitlichen Ergebnisse. Während in einer Arbeit aus den Niederlanden die F2F-Behandlung ei-ner internetbasierten Behandlung mit Therapeutenunterstützung per E-Mail deutlich überlegen war [32], war diese Überlegenheit etwas geringer in einer Studie an US-Militärangehörigen ausgeprägt, in der eine F2F-Behandlung mit einer internetbasierten Behandlung ohne Therapeutenunterstützung verglichen wurde [48]. In einer anderen Arbeit zeigte sich eine Nicht-Unterlegenheit einer internetbasierten Behandlung mit Therapeutenunterstützung per E-Mail und Telefonkontakten mit einer Gruppenbehandlung im F2F-Format [7].…”
Section: Randomisierte Kontrollierte Studienunclassified
“…Direkte Vergleichsstudien von internetbasierter KVT-I zu F2F-psychotherapeutischer Behandlung zeigten bislang keine ganz einheitlichen Ergebnisse. Während in einer Arbeit aus den Niederlanden die F2F-Behandlung ei-ner internetbasierten Behandlung mit Therapeutenunterstützung per E-Mail deutlich überlegen war [32], war diese Überlegenheit etwas geringer in einer Studie an US-Militärangehörigen ausgeprägt, in der eine F2F-Behandlung mit einer internetbasierten Behandlung ohne Therapeutenunterstützung verglichen wurde [48]. In einer anderen Arbeit zeigte sich eine Nicht-Unterlegenheit einer internetbasierten Behandlung mit Therapeutenunterstützung per E-Mail und Telefonkontakten mit einer Gruppenbehandlung im F2F-Format [7].…”
Section: Randomisierte Kontrollierte Studienunclassified
“…One study directly comparing face-to-face CBT with dCBT demonstrated that face-to-face CBT outperformed dCBT [ 43 •]. A later study in military personnel confirmed this [ 50 ]. A comparison of dCBT against group CBT did however not show any significant differences in improvement in insomnia [ 24 ].…”
Section: Evidence For Dcbt For Insomniamentioning
confidence: 96%
“…The 5-point Likert scale is used to rate each item (e.g., 0 = no problem; 4 = very severe problem), yielding a total score ranging from 0 to 28. The total score is interpreted as follows: absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15-21); and severe insomnia (22-28) (51). The response criterion is determined as decrease of the ISI score of more than 7 points compared to baseline (52).…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…In direct comparisons, individual face-to-face CBT-I showed better outcomes than internet-based CBT-I (iCBT-I) (13,14).…”
Section: Introductionmentioning
confidence: 95%